A new subspecies and taxonomic notes on Passiflora L. (Passifloraceae) in Brazilian Amazon, Mato Grosso, Brazil - Koch, Ana Kelly; Engels, Mathias Erich; Reis, Nilmária Natália Veras; Soares-Lopes, Célia Regina Araújo (Phytotaxa, 2019)
A new subspecies of Passiflora garckei (Passifloraceae) in Brazilian Amazon is described and illustrated. Furthermore, the lectotype of P. gardneri is herein designated and its geographical distribution is expanded to the state of Mato Grosso, Brazil.